2005
DOI: 10.1523/jneurosci.4023-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Thalamocortical Synapse Reorganization from Subplate to Layer IV during Postnatal Development in theReeler-Like Mutant Rat (Shaking Rat Kawasaki)

Abstract: Transient synapse formation between thalamic axons and subplate neurons is thought to be important in thalamocortical targeting.Shaking rat Kawasaki (SRK), having reversed cortical layering similarly observed in reeler mouse, provides an interesting model system to test this idea. The spatial and temporal pattern of excitation was investigated using optical recording with voltage-sensitive dyes in thalamocortical slice preparations from SRK. At postnatal day 0 (P0), a strong optical response was elicited withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…This finding suggests the existence of highly specific cell-autonomous target selection mechanisms that control synapse formation in this strongly topographic pathway, and is not compatible with a singular concept based on gradients of attractive and repulsive molecules (7,53). These results further support our notion that the reeler cortex is not simply inverted, and question findings of a concomitantly inverted thalamocortical projection (33,54). Moreover, probabilistic mapping of the TC projections in subcortical and cortical areas and the MiR axonal tracing revealed a striking feature of the reeler cortex: the formation of a unique columnar-like termination pattern of the TCP.…”
Section: Validation Of In Vivo Probabilistic Tcp With Correlative Axonalmentioning
confidence: 57%
“…This finding suggests the existence of highly specific cell-autonomous target selection mechanisms that control synapse formation in this strongly topographic pathway, and is not compatible with a singular concept based on gradients of attractive and repulsive molecules (7,53). These results further support our notion that the reeler cortex is not simply inverted, and question findings of a concomitantly inverted thalamocortical projection (33,54). Moreover, probabilistic mapping of the TC projections in subcortical and cortical areas and the MiR axonal tracing revealed a striking feature of the reeler cortex: the formation of a unique columnar-like termination pattern of the TCP.…”
Section: Validation Of In Vivo Probabilistic Tcp With Correlative Axonalmentioning
confidence: 57%
“…It was further shown that TCA can correct an altered development both during their subcortical trajectory (Higashi et al, 2005) as well as their subsequent growth within cortex (for review, see Rash and Grove, 2006). Although our observations are made in adulthood, it seems that the BRL mutation has neither influenced the subcortical trajectory, nor the termination of TCAs in the appropriate cortical layers.…”
Section: Discussionmentioning
confidence: 75%
“…This seems to ensure the building of the basic cortical module, i.e., the column (Mountcastle, 1997;Douglas and Martin, 2007;Petersen, 2007). Part of this developmental plasticity could be mediated by the proper interaction of early thalamic axons with subplate neurons (Higashi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although several lines of evidence since then have suggested at least a substantial additional smearing of inverted layer borders caused by wrongly positioned cells, the concept of inversion is still frequently used to interpret findings in reeler (D'Arcangelo, 2005;Higashi et al, 2005;Strazielle et al, 2006).…”
Section: Discussionmentioning
confidence: 99%